Quantitative determination of 1,2‐diacylglycerol in thoracic aorta of the rat using latroscan TLC/FID: Effect of norepinephrine - Okumura, Kenji; Yamada, Yumiko; Kondo, Junichiro; Kobayashi, Norio; Hashimoto, Hidekazu; Ito, Takayuki (Lipids, 1989)
This study was undertaken to evaluate the use of the Iatroscan TLC/FID system for quantitating 1,2‐diacylglycerol (DG) in the aorta. Cholesteryl acetate was chosen as an internal standard. In order to avoid interference of triglyceride and phospholipids with the separation of the internal standard and 1,2‐DG, a stepwise elution of lipids from the silicic acid column was used. The development of Chromarods was done using two solvent systems and a three‐step developing technique. Assay and recovery of both 1,2‐DG and cholesterol (as compared to cholesteryl acetate) were sufficient to measure changes in the 1,2‐DG content in blood vessels. After exposing the thoracic aorta to 10−5 M norepinephrine for 10 min, the 1,2‐DG content increased nearly two‐fold without significant change in cholesterol content.